Organizational change in the United States Forest Service: the role of community collaboration - Orth, Patricia Biddle, author; Cheng, Antony S., advisor; Fernandez-Gimenez, Maria E., committee member; Reid, Robin S., committee member; Taylor, Peter L., committee member (Colorado State University. Libraries, 2015)
Over the last three decades, collaboration has come to the fore as a way to address natural resource management problems that are often complex and contentious. As such, a new way of doing business has emerged for the United State Forest Service (USFS) as it engages community members in collaborative governance arrangements created to address forest management issues. USFS field-level personnel and the community stakeholders involved in collaborative governance arrangements expend valuable and limited resources to obtain collaborative outcomes. Field observations suggest that in order for collaborative outcomes to be durable and maintain longevity, changes must occur at the organizational level. However, few existing studies that document organizational changes made by natural resource land management agencies as a result of the agency's engagement in collaborative governance arrangements with community stakeholders. This dissertation provides theoretical and practical insights into the organizational changes occurring at three USFS field offices. This exploratory, qualitative study employs a case study approach and semi-structured interviews were conducted with agency personnel and non-agency stakeholders. Document analysis of meeting minutes and personal observation data were also conducted. The data yielded the richest results when interpreted through three overarching theoretical lenses: organizational change, public administration, and collaborative governance. The results revealed that organizational changes are occurring at the field-level as a result of the actions of individual actors as they cross organizational boundaries. The outcomes of these changes can be beneficial to the agency, but a cautionary tale is presented suggesting that collaborative processes may impede, if not derailed, by power imbalances. The role of trust, or more accurately, the lack thereof, and its ability to change organizational boundaries and create power imbalances in the shared decision-making arena emerged as finding of importance to land managers and collaborative governance theory. This dissertation advances the scholarly and practical knowledge of organizational change by presenting empirical evidence of the impact of community collaboration on federal natural resource agencies. It is necessary for the leadership of the USFS to understand their role in the collaborative process and to understand how and why these changes are taking place if they are to be sensitive to the added pressures and tensions that collaboration brings to their individual staff members. Managers in the USFS will need to be cognizant of the attributes of trust and should encourage their staff to build trust with stakeholders if they wish to maintain equitable power positions in the shared decision-making process. Future research that provides evidence of the linkage between organizational change, trust, and power would be useful in further understanding how the collaborative process and the collaborative behavior of individuals in natural resource management links to the outcomes of collaboration.